The arid and semiarid low lands of Ethiopia: Environments, pastoral economies and issues in natural resources sustainability - Coppock, D. Layne (Institute of Agricultural Research, 1990)
Ethiopia has a vast lowland area that is important for human subsistence and the national economy. This paper reviews the physical and biological features of the lowlands and some Development perspectives that have been pursued since the 1970s. As elsewhere in Ethiopia, the lowlands have growing populations of people and livestock that might be responsible for resource degradation in the form of overgrazing and dryland cultivation. A third factor of degradation, bush encroachment, is the combined effect of overgrazing and lack of fire management. The solutions to these problems vary in difficulty, though all would principally involve pastoral participation in problem-solving, local administrative facilitation, and reevaluation of some national resource management policies. The latter includes the need to formulate regional landuse guidelines, with local loosening of restrictions to permit range burning or regulated charcoal production (where appropriate), thereby to enhance the quality of some vegetation communities. Of all problems, overstocking is the most difficult to solve. This arises from a human population that is still subsistence-oriented and has little other alternatives than invest resources in livestock. Options to help ameliorate this problem may include more pay-as-you-go Development activities to stimulate cash demand, and possibly raising livestock prices to increase offtake. Until the economy is in a position to offer attractive alternatives to livestock-based subsistence and investment, the specter of overstocking in some lowland areas will not be avoided